(3GdhSjdI aj GdMSGHs - (3CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,TgGH GdOjf, J (B815 (3g` s; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s ((3eMeO Hf CHj HcQ GdHdHjSi GdTGaYi s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg YOO fYeGFg s
(3BNQgG (B:s
(3hef GQGO GdJHMQ ai gPG Gdaf hGdhba Ydi eG jfai GdZdjd aYdjg (B" (3HGdeYhfI(B" s
(3aj UfGYI GdMSGH GdghGFjs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdQjGVjGJs